Dynamic response of proton exchange membrane fuel cell under mechanical vibration. (28th September 2016) - Wang, Xueke; Wang, Shubo; Chen, Sitong; Zhu, Tong; Xie, Xiaofeng; Mao, Zhiming
Abstract: The dynamic response of proton exchange membrane fuel cells (PEMFCs) under mechanical vibration is an important criterion in the application to automotive systems. The effect of mechanical vibration on dynamic response was investigated on an automobile vibrating platform. The PEMFC voltage was acquired according to the current density change under a variety of amplitude, frequency and air stoichiometry. Furthermore, liquid water formation and transport were investigated under the mechanical vibration by employing a transparent PEMFC. The results show that a new steady-state of the voltage under vibration and no vibration take about 50s and 20s respectively after the current density step. The PEMFC dynamic performance was slightly improved under amplitude at 4 mm, compared to operation at no vibration. Also, the voltage fluctuation was detected under the vibration, the small droplets merged into larger droplets is due to the sudden vibration. These larger droplets interfere with the mass-transfer process in the gas channels. Highlights: The effect of mechanical vibration on dynamic response of PEMFC was investigated. Liquid water formation and transport were investigated under the mechanical vibration. The vibration causes the voltage oscillations of PEMFC is larger than under no vibration.